Isolated intraparenchymal tension pneumocephalus - Soin, Priti (Proc (Bayl Univ Med Cent), 2018)
Pneumocephalus after trauma is not uncommon but rarely develops into tension pneumocephalus. Delayed-onset spontaneous tension pneumocephalus is rare, and delayed-onset isolated intraparenchymal/intracerebral tension pneumocephalus is even more so. We describe a 35-year-old man who presented with urinary incontinence, left eye vision loss, and nasal discharge/cerebrospinal fluid rhinorrhea 2 months after recovering from bifrontal hemorrhagic contusions following a road traffic accident. Intraparenchymal/intracerebral tension pneumocephalus was diagnosed with computed tomography and the patient was taken for an urgent decompressive surgery along with repair of the skull base defect.